A contribuição do projeto "Círculo de leitore" para a formação de leitores no contexto da biblioteca do Instituto Federal de Estudos do Trópico Úmido - IETU UNIFESSPA - PA. - Silva, Maria José Pereira da (2023)
As an essential factor for the human development, reading is a lesson that should be priority at the beginning and during school and academic life of every student. Despite being a recurring preoccupation for the elementary, middle and high school education systems, many students are arriving at the university without more advanced reading skills and competences, which affects negatively in their learning in higher education systems. In view of this scenario, projects of literary reading that cultivate the reading habit among academics are necessary, so that they can grow their knowledge and personal development, and thus becoming more critics and intellectuals who think for themselves. In this context, the library is one of the important spaces of reading intervention that it needs to be, constantly, active with literary reading projects. Thus, this work was made aiming to verify the relevance and possibility of a project of readers’ formation in the library of the Institute for the Studies of the Humid Tropics (IETU) of the Federal University of the South and Southeast of Pará (UNIFESSPA-PA). The research is qualitative, quantitative, bibliographic, documentary and interpretative. Methodologically, semi-structured questionnaires were used. Also, to understand the user profile of the library, some institutional documents like the book lending registry were analyzed in order to demonstrate the relationship between the students, literary books and the library. Regarding the theoretical foundation, the following author was used as research methodology: Thiollent (1985), and the contributions of Cosson (2006) as well on the structuring of reading groups. Lajolo (2002); Paulino (2005); Yunes (1995, 2003 e 2012); Jouve (2002, 2013); Cosson (2006, 2019); Compagnon (2003); Candido (2004) and Azevedo (2004) can also be highlighted when it comes to understanding the reader/literary formation. To discuss matters about university libraries and readers’ circles, Soares (2009), Silva (1987, 1997); Roca (2012); Pereira Júnior (2019); Bortolin (2006); Bortolin and Almeida Jr. (2011); Bortolin and Santos (2014); Silva et al (2015); Silva (1987, 1997), Cosson (2014); Fontes (2012); Almeida Jr (1997) and Milanese (2008), among others, were relied upon, as they describe in their theories the function of the library in its literary readers’ formation role through projects involving reading groups. Results include the contribution that the activities of literary reading implemented by the library of the unity IETU/UNIFESSPA-PA had on the reading formation of the group and in the effectiveness of the librarian as a reading interventionist. The results also show the importance of activities of readers’ formation, as well as the contribution of the library in taking these activities to the academic community and the community in general, which, consequently, evince literature as fundamental in the life of students.